Freedom of printing press: a legal review of Printing Presses and Publications Act 1984 / Muhammad Haris Abdul Rahim ...[et al.] - Abdul Rahim, Muhammad Haris; Suhairi, Ilya Fatanah; Dicky, Siti Mahsuri; Zamri, Nurul Akmar (2014)
This research paper seeks to examine the particular statute which governs printing presses in Malaysia which is the Printing Presses and Publications Act 1984. Further this research paper proposed some recommendations in order to promote freedom of press in Malaysia. The Printing Presses and Publications Act 1984 requires a news publisher to obtain publishing permits before publishing newspapers. The regulations of newspaper in Malaysia are conducted by the Home Minister which empowers him the right to grant or refuse an application for publishing permit. He further had the power to revoke and suspend a publishing permit for any period he considers desirable. Through Doctrinal legal research and Doctrine of Empirical research we could infer whether the Printing Presses and Publications Act 1984 has been able to meet its objective of ensuring the freedom of the press in a plural society in order to achieve positive news reporting and open up the minds of the people in Malaysia. Through the data collected by the study of legal statute, court's decision, a few established websites, questionnaire and interviews, we can identify whether the said act is good as it is or needs further improvement. We have also looked into the laws and regulations in other countries, namely Sweden and Australia where the regulations have been observed and critically analysed and compared with the enforcement in Malaysia. Based on the analysis, we adopt the idea of abolishing the licensing requirement and for the establishment of an independent press council to deal with complaints against the press.